2016
DOI: 10.1007/5584_2016_212
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between 25(OH)D and IGF-I in Children and Adolescents with Growth Hormone Deficiency

Abstract: Recent studies have shown that vitamin D has an impact on the production and secretion of IGF-I in the liver. The aim of our study was to investigate the relationship between the concentrations of 25-hydroxy vitamin D [25(OH)D] and insulin-like growth factor I (IGF-I) in growth hormone deficient children and adolescents before recombinant human growth hormone (rhGH) treatment. The study was retrospective and included 84 children and adolescents aged 4-17. Prior to initiating rhGH therapy, concentrations of 25(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Epidemiological studies have suggested that serum IGF-1 level correlates with fracture risk, bone density and bone mass (Rosen, 2004;Niu et al, 2005;He et al, 2006;Léger et al, 2007;Locatelli et al, 2014;Devesa et al, 2016). Several authors have evaluated the association between the GH/IGF-1 axis and vitamin D status (Gómez et al, 2004;Bogazzi et al, 2011;Ameri et al, 2013;Witkowska-Sędek et al, 2016;Ciresi et al, 2017;Trummer et al, 2017). The study by Ameri et al (2013) showed that vitamin D could increase circulating IGF-1 level in adults and better vitamin D status may facilitate the achievement of normal IGF-1 values in GHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have suggested that serum IGF-1 level correlates with fracture risk, bone density and bone mass (Rosen, 2004;Niu et al, 2005;He et al, 2006;Léger et al, 2007;Locatelli et al, 2014;Devesa et al, 2016). Several authors have evaluated the association between the GH/IGF-1 axis and vitamin D status (Gómez et al, 2004;Bogazzi et al, 2011;Ameri et al, 2013;Witkowska-Sędek et al, 2016;Ciresi et al, 2017;Trummer et al, 2017). The study by Ameri et al (2013) showed that vitamin D could increase circulating IGF-1 level in adults and better vitamin D status may facilitate the achievement of normal IGF-1 values in GHD.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the GH/IGF-1 axis on bone turnover can be evaluated using the measurement of bone turnover markers (BTMs), including ALP and BALP (Ono et al, 1996;Locatelli et al, 2014;Devesa et al, 2016). The GH/IGF-1 axis can modulate vitamin D metabolism and, conversely, vitamin D can influence IGF-1 concentrations (Soliman et al, 2008;Bogazzi et al, 2011;Ameri et al, 2013;Ciresi et al, 2014;Witkowska-Sędek et al, 2016;Ciresi et al, 2017;Schwetz et al, 2017). Activation of vitamin D receptor (VDR) localised in osteoblasts, osteocytes, chondrocytes, and osteoclasts regulates cell proliferation, maturation, and mineralization as well as bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported significantly higher values in the sunny season (31.1 ± 11.1 ng/mL in June–September) than in the cold season (17.3 ± 5.3 ng/mL in November–February), with 35% having vitamin D insufficiency and 40% vitamin D deficiency. Witkowska-Sedek et al evaluated 84 children and adolescents with GHD and found low 25OHD concentrations (22.3 ± 6.9 ng/mL) [ 32 ], and Savanelli et al evaluated 41 adult GHD patients and found mean 25OHD concentration of 21.3 ± 12.3 ng/mL, with vitamin D deficiency present in 51% of the patients compared to 14.6% of the controls [ 33 ]. In addition, Ameri et al evaluated 69 adult GHD patients, most with postsurgical hypopituitarism [ 34 ], and found that only 6 patients (8.7%) had a serum 25OHD concentration above 30 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, reduced 1,25(OH)2-D3 or 25OH-D3 levels in children with GHD have also been demonstrated [29,30]. Ciresi et al found that 40% of Sicilian children with GHD at baseline had vitamin D deficiency and 35% had vitamin D insufficiency, respectively [31].…”
Section: Impact Of Ghd On Vitamin D Levelsmentioning
confidence: 99%